Histological analysis provides further insights into Harpagifer antarcticus reproductive biology at the western Antarctic Peninsula - Novillo Estofan, Julio Manuel; Moreira, María Eugenia; Macchi, Gustavo Javier; Barrera Oro, Esteban (Polar Biology)
Prior understanding of Harpagifer antarcticus reproductive biology was based exclusively on macroscopic observations of its gonadal maturation cycle. Our present study with H. antarcticus specimens collected in summer of 2019 at Paradise Bay (PB), Western Antarctic Peninsula (WAP), provides a) additional reproductive parameters, and b) for first time, a histological analysis of the gonads, clarifying understanding of the spawning period of the species in the area. In females the gonado-somatic index was 5.3–19.6%, leading clutch oocytes was 0.94–1.95 mm, and total fecundity ranged between 408 and 1723 oocytes/female (X ± SD = 794 ± 328, n = 22). The histology allowed the identification of gravid females with oocytes in late vitellogenesis with evidence of ongoing hydration processes and spent females with post-ovulatory follicles. The presence of spermatozoa in mature testes indicated that the males were in developing and ripe condition. Our reproductive data for H. antarcticus at PB, validated with histology, indicate that the species was in spawning during summer, in agreement with a previous report of a late spring–summer spawning for the species at the same site. Literature data indicate that at the South Orkney Islands, H. antarcticus spawns three months earlier (May–June), probably associated with differential environmental factors between this area and the WAP. Our findings support the hypothesis that the life cycle characteristics of H. antarcticus—e.g., low fecundity and short pelagic phase—promote the isolation of populations as reflected in differences in the reproductive timing. Fil: Novillo Estofan, Julio Manuel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Moreira, María Eugenia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Cientifico Tecnolológico Mar del Plata. Instituto de Investigaciones en Biodiversidad y Biotecnología. ...